2005
DOI: 10.2320/jinstmet.69.667
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Residual Stress Induced by Ar Ion Irradiation on Magnetostriction of R-Fe(R: Tb, Sm) Thin Film

Abstract: Magnetostrictive properties of Ar ion irradiated R Fe(R: Tb, Sm) thin films were studied with respect to residual stress. Film samples were prepared by a magnetron sputtering. The film composition was Tb 36 Fe 64 and Sm 27 Fe 73 with amorphous structures. After the deposition, film samples were irradiated by Ar ions with an energy of 10 keV and a current density of 27 80× 10 -2 A/m 2 up to 1×10 22 ions/m 2 . Magnetostrictive susceptibility of the Tb 36 Fe 64 film decreased with increasing ion current densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The composition of the Sm-Fe lms were about Sm 22 Fe 78 determined by WDX. This composition on Sm-Fe system is presumed to form two phase alloy include Sm 2 Fe 17 phase and SmFe 3 phase by phase diagram.…”
Section: Xrd and Wdx Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The composition of the Sm-Fe lms were about Sm 22 Fe 78 determined by WDX. This composition on Sm-Fe system is presumed to form two phase alloy include Sm 2 Fe 17 phase and SmFe 3 phase by phase diagram.…”
Section: Xrd and Wdx Analysismentioning
confidence: 99%
“…21) Takeuchi et al suggested that the magnetostrictive susceptibility of the thin lms increased with decreasing magnetic anisotropy energy due to increasing the compressive stress. 22) Accordingly, this improve of the dλ/dH can be caused by a development of the in-plane magnetic anisotropy induced by the increase of compressive stress.…”
Section: Xrd and Wdx Analysismentioning
confidence: 99%
“…Furthermore, magnetostrictive materials forms single domain by making it to amorphous. The domain structure of the magnetostrictive amorphous consists mainly of a single domain inner core with the magnetization [3]. However, the magnetostrictive materials actually used are not complete amorphous but contain the crystalline phase, which becomes the nucleus of the domain formation.…”
Section: Introductionmentioning
confidence: 99%